WEB-BASED UI/UX DESIGN FOR THE SCHOOL LIBRARY OF SMA NEGERI 1 UJAN MAS BASED ON DESIGN THINKING METHODE - Rifqi Haidar Al-Aziz (Jurnal Sistem Informasi dan Bisnis Cerdas, 2025)
SMA Negeri 1 Ujan Mas is a public school founded by the Muara Enim Regency government to overcome the shortage of high schools in the area. Currently, library management is still done manually, which results in difficulties in searching for book data, accumulation of documents, and the risk of data loss. This research aims to design a web-based library user interface (UI/UX) using the Design Thinking method. With a computerized library system, it is hoped that it can increase the efficiency of library management and provide better access for students and school staff. System testing was carried out using the System Usability Scale (SUS), which is a system usability assessment method based on a survey with 10 questions using a Likert scale. Test results from 31 respondents showed an average SUS score of 76.21. Based on the interpretation of the SUS value, this prototype is on the grade scale B and is categorized as Good in the adjective rating assessment. Testing of the prototype showed that this system was well received by target users, both students and teachers. The prototype has met user needs in terms of function and aesthetics, in accordance with effective and efficient design principles, so that it can be a solution for library management at SMA Negeri 1 Ujan Mas.